On A Method of Estimating the Hidden Population of Drug Addicts - A.O. Ilesanmi , S.O. Adejuwon , O.Y. Halid (International Journal of Emerging Trends in Science and Technology, 2018)
The consumption of drugs like Tramadol, skutches, Skunk, Loud and Indian hemp are illegal in Nigeria and the increasing addiction of youth to drugs of different forms is very evident in the society. This trend is of great concern with no effective approach to deal with the problem primarily because it involves a hidden population. This study considered the estimation of the hidden population size of drug addicts in Ekiti state, Nigeria between 2015 and 2016, using Capture-Recapture (C-R) method. Two data sources namely National Drug Law Enforcement Agency (NDLEA) and psychiatric unit of Ekiti State University Teaching Hospital (EKSUTH) were used and The lists of individuals collected from the two data sources were used to estimate the population size by identifying the number of individuals that appeared in one or two of these lists. Results showed that the estimated hidden population size of drug addicts in Ekiti State during the study period is 201 leading to the total population of 558 with a 95% confidence interval (486, 636).